The Effects of Ambient Temperature on Lumbar Disc Herniation: A Retrospective Study - Wang, Ping; Chen, Cai; Liu, Fanjie; Bu, Fan; An, Jianpeng; Qin, Hao; Zhang, Qinghao; Wang, Tao; Cao, Shengnan; Li, Wei; Shi, Bin (Frontiers in Medicine, 2022)
Purpose This article was designed to provide critical evidence into the relationship between ambient temperature and intensity of back pain in people with lumbar disc herniation (LDH). Methods Data concerning patient's age, gender, diagnostic logout, admission time, discharge time, residence area, and work area (residence area and work area were used to ensure research area) from 2017 to 2019 were obtained from the Neck-Shoulder and Lumbocrural Pain Hospital in Jinan, China. A total of 1,450 hospitalization records were collected in total. The distributed lag non-linear model (DLNM) was used to evaluate the relationship between lag–response and exposure to ambient temperature. Stratification was based on age and gender. Days 1, 5, 20, and 28 prior to admission were denoted as lags 0, 5, 20, and 28, respectively. Results An average daily temperature of 15–23°C reduced the risk of hospitalization the most in men. Conversely, temperatures <10°C drastically increased hospitalization in men, particularly in lags 0–5 and lags 20–28. Men aged between 40 and 50 years old showed less effect in pain sensation during ambient temperature. Conclusion High or low ambient temperature can increase the hospitalization risk of LDH, and sometimes, the temperature effect is delayed.